S100 proteins as a key immunoregulatory mechanism for NLRP3 inflammasome - Acter, Shahinur; Lin, Qing (Frontiers in Immunology, 2025)
The S100 superfamily of proteins consists of Ca2+-binding proteins characterized by the EF-hand motif. Certain members of this protein family, such as S100A8, S100A9, and S100A12, have been effectively utilized as biomarkers for the detection and evaluation of prognosis in immunological diseases. These proteins are also identified as damage-associated molecular pattern (DAMP) molecules, which exhibit significant upregulation in various autoimmune disorders, cancers, and neurodegenerative diseases. Following tissue injury, necrotic or immune cells release or secrete DAMPs to initiate inflammatory responses. This signaling further creates autocrine and paracrine positive feedback loops that amplify and sustain the inflammatory response. The NLRP3 inflammasome pathway is a pivotal component in these DAMP-induced immune regulatory mechanisms. This review summarizes the regulatory roles of S100 protein family in NLRP3 inflammasome signaling and their functions in innate and adaptive immunity, with an emphasis on pulmonary hypertension. Moreover, we examine the interactive feedback mechanisms among NLRP3 inflammasome, S100A8/A9, and Gasdermin D, exploring their implications in autoimmune diseases.